Amazing animals : a spin & spot book - Charlesworth, Liza; Reese, Brandon (New York : Scholastic, 2017)
"Discover more than 60 animals in their amazing habitats with the turn of a page and the spin of a wheel! Spin the wheel, spot the picture, and read along!"--Back cover.
On board pages with moveable spin wheels.
Pre-K.
Keywords: Animals -- Juvenile literature